Polyamine Requirements of a Conditional Polyamine Auxotroph of Escherichia coli - Munro, George F. (1973)
Escherichia coli MA-159 is deficient in agmatine ureohydrolase. After addition of exogenous arginine, the cellular putrescine content declines immediately and exponentially; however, the spermidine content remains normal for 3 h. The growth rate of such cultures, measured turbidometrically, slows gradually over many hours. Putrescine-depleted cultures grow especially slowly in media of low osmolarity, whereas nondepleted cultures grow at similar and rapid rates in media of either normal or low osmolarity. External osmolarity also affects the ability of various exogenous polyamines to stimulate growth of putrescine-depleted cultures. In medium of normal osmolarity, putrescine and spermidine both allow sustained rapid growth for many hours. In low osmolarity medium, putrescine allows sustained rapid growth, whereas cultures containing spermidine grow more slowly; this result cannot be explained by conversion of putrescine to spermidine, for cultures grown with exogenous putrescine contain smaller spermidine pools than do cultures grown with exogenous spermidine. Spermine greatly stimulates growth in medium of normal osmolarity; however, in medium of low osmolarity, spermine is much less effective and can block the action of putrescine. Several other polyamines have been studied in this system. These results confirm and expand previous reports that polyamines are necessary for growth of E. coli and suggest that putrescine may have a specific function during growth in media of low osmolarity.